Roles of circRNA dysregulation in esophageal squamous cell carcinoma tumor microenvironment - Li, Jingyi; Song, Yuxia; Cai, Huihong; Zhou, Bo; Ma, Jun (Frontiers in Oncology, 2023)
Esophageal squamous cell carcinoma (ESCC) is the most prevalent histological esophageal cancer characterized by advanced diagnosis, metastasis, resistance to treatment, and frequent recurrence. In recent years, numerous human disorders such as ESCC, have been linked to abnormal expression of circular RNAs (circRNAs), suggesting that they are fundamental to the intricate system of gene regulation that governs ESCC formation. The tumor microenvironment (TME), referring to the area surrounding the tumor cells,is composed of multiple components, including stromal cells, immune cells, the vascular system, extracellular matrix (ECM), and numerous signaling molecules. In this review, we briefly described the biological purposes and mec hanisms of aberrant circRNA expression in the TME of ESCC, including the immune microenvironment, angiogenesis, epithelial-to-mesenchymal transition, hypoxia, metabolism, and radiotherapy resistance. As in-depth research into the processes of circRNAs in the TME of ESCC continues, circRNAs are promising therapeutic targets or delivery systems for cancer therapy and diagnostic and prognostic indicators for ESCC.